Does nematic order allow groups of elongated cells to sense electric fields better? - Kurmanbek Kaiyrbekov; Brian A. Camley (PLoS ONE, 2025)
Collective response to external directional cues like electric fields helps guide tissue development, regeneration, and wound healing. In this study we focus on the impact of anisotropy in cell shape and local cell alignment on the collective response to electric fields. We model elongated cells that have a different accuracy sensing the field depending on their orientation with respect to the field. With this framework, we assume cells are better sensors if they can align their long axes perpendicular to the field. Elongated cells often line up with their long axes in the same direction — “nematic order” – does a nematic cell-cell interaction allow groups of cells to share information about their orientation to sense fields more accurately? We use simulations of a simple model to show that if cells orient themselves perpendicular to their average velocity, alignment of a cell’s long axis to its nearest neighbors’ orientation can in some circumstances enhance the directional response to electric fields. We also show that cell-cell adhesion modulates the accuracy of cells in the group.